(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Acute tinnitus, characterized by the perception of persistent ringing or noise in the ears without an external sound source, poses significant challenges for patients and healthcare providers. This article explores the aetiology, pathophysiology, and current diagnostic methods associated with acute tinnitus. Emphasis is placed on the latest advancements in treatment strategies, including pharmacological therapies, sound-based interventions, and cognitive-behavioral approaches. The role of multidisciplinary management and the potential of emerging technologies such as neuromodulation and artificial intelligence in improving treatment outcomes are also discussed. By synthesizing current evidence, this study provides practical insights into optimizing care for patients suffering from acute tinnitus and highlights directions for future research in this field.